Editorial [Hot Topic: Hot Topics in Cellular Cardiac Electrophysiology with Potential Impact on Future Drug Design (Guest Editors: Peter P. Nanasi and Valeria Kecskemeti)] - P. Nanasi, Peter; Kecskemeti, Valeria (Current Medicinal Chemistry, 2011)
Development of more and more effective antiarrhythmic agents has been in the focus of interest of drug research during the last four decades. The ideal omnipotent compound, however, has not been shown up so far. The currently applied antiarrhythmic strategies largely follow the classic scheme of Vaughan Williams [1], which has been modified several times since its first publication [2, 3]. According to this classification, class 1 drugs suppress action potential upstroke and intraventricular conduction velocity due to inhibition of fast sodium channels in a use-dependent manner. Class 2 agents block beta-adrenergic receptors, resulting in reduction of intracellular cAMP level, and consequently, the activity of several cAMP-activated ion channels. Class 3 compounds prolong action potential duration, and consequently, the refractory period, decreasing this way the probability of formation of re-entrant circuits. Class 4 drugs are calcium channel antagonists reducing Ca2+ entry into cardiac cells, which, in turn, improves impulse propagation and helps to prevent the development of triggered activity in Ca2+- loaded myocardium. Each of these antiarrhythmic mechanisms, however, may also carry serious proarrhythmic risks [4]. For instance, prolongation of action potentials due to class 3 antiarrhythmic action increases Ca2+ content of cardiac cells and facilitates reactivation of ICa. These mechanisms are responsible for generation of late and early afterdepolarizations, respectively [5, 6]. Class 1 agents, especially those having slow turn-off kinetics, likely impair conduction of normal impulses as well [7], which is also believed to be proarrhythmic [4]. Similarly, inhibition of ICa - either as a consequence of a beta-adrenergic blockade, or directly, due to application of Ca2+ entry blockers - may slow conduction in nodal tissues. Most of these theoretical considerations are unfortunately supported by results of clinical trials, where many antiarrhythmics have been shown to increase mortality. The increased mortality observed in the CAST study [8] with 1/C agents may primarily be associated with proarrhythmic effects of these drugs, although their negative inotropic action leading to heart failure may also have been involved. The increased mortality observed in d-sotalol treated patients of the SWORD study [9] was clearly due to the reverse rate-dependent torsadogenic action of the compound. It could, therefore, be concluded that, in spite of the relative efficacy of many class 3 drugs including dofetilide [10], a new group of selective class 3 agents, devoid of reverse rate-dependent action, should be developed [11]. It is shown by the present work of Banyasz et al. why this concept is not feasible, i.e. application of selective class 3 drugs is not necessarily the optimal treatment of cardiac arrhythmias. In contrast, if suppression of repolarization may be torsadogenic, then assistance of repolarization by enhancement of an outward current, such as IKr, may also exert antiarrhythmic actions. This heretical doctrine is discussed by Szabo et al. in their review article. The controversial experimental and disappointing clinical observations inspired the development of new antiarrhythmic strategies. Accordingly, new potential targets for antiarrhytmic drug therapy, such as manipulation of the endogeneous adenosinergic mechanisms, the Ca2+-activated as well as the ATP-sensitive potassium channels, or suppression of the If pacemaker current, have been emerged. An example for each of these novel approaches are presented in this Special Issue. Since ventricular fibrillation is acutely lethal, most of our efforts to suppress cardiac arrhythmias have been directed to ventricular myocardium. Atrial fibrillation may also be lethal - although at a much longer time scale. However, the quality of life with perpetual of frequently manifesting atrial fibrillation is strongly compromised. The state of art summary of the recent progress in treatment of atrial fibrillation is provided by the excellent paper of Jost et al. If considering the possibilities offered by the somewhat farther future, the precise and detailed understanding of regulation of cardiac ion currents, including the contribution of various signal transduction cascades in this control, may be crucial. Some of these important pathways of regulation (e.g. the adrenergic and purinergic control of the heart) have long been studied; however, recent results may modify the perspectives of their authentic manipulation. The research history of calmodulin kinase - one of the most important mechanism responsible for Ca2plus;- dependent regulation of ion channels in the heart - is not too long, but extremely promising. Cardiac arrhythmias are often combined with electrical remodeling - electrical changes caused by long lasting pathological events. This may alter the density, as well as the kinetic properties of cardiac ion channels, which, in turn, may be important from the point of view of the antiarrhythmic strategy to be applied. Mechanisms involved in long term regulation of L-type calcium channels seen in the presence of calcium channel blockers are highlighted by the study of Magyar et al.....